Empleo de rizobacterias como promotoras de crecimiento vegetal en tres leguminosas forrajeras en el Campo Experimental La Playita campus UTC – La Maná - Pallo Toaquiza, Byron Luciano (2014)
The use of rhizobacteria as stimulators of plant growth in three leguminous forage in the Experimental Field La Playita CTU campus - La Maná, proposed the following objectives: to inoculate the rhizobacteria plant growth promoting, Azotobacter chroococum and Pseudomona fluorecens in the study of leguminous; to identify populations of bacteria and fungi that exist in leguminous for each bacterial inoculant applied in two ages of harvest 45, 60 and 75 days; and to perform bromatological analysis. At complete random design was applied (CRD) in factorial accordance with three leguminous, two inoculators, two sites, three repetitions, and two plants as experimental unit; the planting of leguminous was realized in bags and soil....